BH3‐only proteins: a 20‐year stock‐take. (26th January 2015) - Doerflinger, Marcel; Glab, Jason A.; Puthalakath, Hamsa
Abstract : BH3‐only proteins are the sentinels of cellular stress, and their activation commits cells to apoptosis. Since the discovery of the first BH3‐only protein BAD almost 20 years ago, at least seven more BH3‐only proteins have been identified in mammals. They are regulated by a variety of environmental stimuli or by developmental cues, and play a crucial role in cellular homeostasis. Some are considered to be tumor suppressors, and also play a significant role in other pathologies. Their non‐apoptotic functions are controversial, but there is broad consensus emerging regarding their role in apoptosis, which may help in designing better therapeutic agents for treating a variety of human diseases. Abstract : Since their discovery nearly 20 years ago, BH‐3 proteins have been central to apoptosis research. They have been implicated in apoptosis in response to a variety of physiological stimuli and have been implicated in a great number of diseases. This mini review discusses the current state of knowledge in the field, including some controversial issues and suggestions for future research. Accompanied by a podcast, listen now . Or listen in iTunes